Binding objects to their spatiotemporal context: Age gradient and neuropsychological correlates of What-Where-When task performance. Issue 2 (4th March 2023) - Varela, Vasiliki; Evdokimidis, Ioannis; Potagas, Constantin
Abstract: A number of recent studies have shown that the ability to accurately recall bound object and spatiotemporal aspects of an experienced event develops gradually in children and is greatly impaired in the elderly, reflecting developmental discontinuities in the integrity of the underlying medial temporal lobe network. Using a novel What-Where- When ( WWW ) visuospatial reconstruction task, the experiential memory performance of a group of healthy older adults (aged 60–80) was compared to that of a group of younger adults (aged 20–40). Both groups were equated on their general cognitive ability, their executive functioning, and on the presence of depression, anxiety, and stress symptomatology. As hypothesized, the performance of the older adults in the binding task was significantly lower, with younger participants recalling three times the amount of bound object and spatiotemporal triads than their older counterparts. Psychomotor speed was found to be lower in older adults and was the only neuropsychological index to significantly affect success on the WWW binding task. Based on this and other relevant studies, the selective associative memory impairment obtained using a non-verbal What-Where-When paradigm emerges as a marker for the detection of early pre-clinical signs of experiential memory pathology.